The prevalence and relevance of adrenal masses in patients with sporadic gastroenteropancreatic neuroendocrine tumours (GEP‐NET). (1st April 2013) - Kanakis, George; Kamp, Kimberly; Tsiveriotis, Konstantinos; Feelders, Richard A.; Zormpala, Alexandra; de Herder, Wouter W.; Kaltsas, Gregory
Summary: Objective: The widespread application of abdominal computerized tomography (CT) imaging has revealed that 0·98–4·0% of individuals harbour adrenal lesions (incidentalomas). There is, however, paucity of information regarding the prevalence of adrenal lesions in patients with gastroenteropancreatic neuroendocrine tumours (GEP‐NETS). Purpose of this study was to estimate the prevalence of adrenal lesions in patients with GEP‐NETS and identify their radiological features and clinical significance. Design: The prevalence of adrenal lesions was estimated retrospectively in 438 patients with GEP‐NETS who underwent abdominal imaging. Secretory status and changes in size were documented during subsequent follow‐up. MEN‐1 patients and ectopic ACTH‐secreting tumours were excluded. Results: Adrenal lesions were detected in 32 (8·4%) of 383 patients included. The majority (22 patients – 69%) were located at the left adrenal gland and the mean size was 23·6 mm. In two patients, one with a well and another with a poorly differentiated tumour, clinicopathological features suggested adrenal metastases. During a mean follow‐up period of 69·5 months, no subsequent growth of any adrenal lesion was observed. Endocrine evaluation documented subclinical glucocorticoid hypersecretion in 4 cases (14%). The presence of adrenal lesions did not correlate to distant metastases, however, they were observed more frequently in patients with G3 tumours. Conclusion: The prevalence of adrenal lesions in patients with GEP‐NETs was found to be higher than the general population and mostly represent benign adrenal adenomas (except patients with G3 tumours). Nevertheless, individualized assessment of imaging characteristics should be still considered.